Hadith #1333 - Sunan al-Nasa'i - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hind bint al-Harith al-Farasiyya هند بنت الحارث الفراسية; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي; Umm Salamah; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan al-Nasa'i)
The Prophet (ﷺ) prayed three (rak’ahs) then said the taslim. Al-Khirbaq said: “You prayed three.” So he led them in praying the remaining rak’ah, then he said the taslim, then he did the two prostrations of forgetfulness, then he said the taslim (again).
Grade:

Hadith #985 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Ahmed bin 'Abdul Malik bin Waqid أحمد بن عبد الملك بن واقد; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hind bint al-Harith al-Farasiyya هند بنت الحارث الفراسية; Ibrahim bin Sa'd bin Ibrahim إبراهيم بن سعد بن إبراهيم; Umm Salamah (Sunan Ibn Majah)
“I came to the Messenger of Allah (ﷺ) and said: ‘Is there any time that is more beloved to Allah than another?’ He said: ‘Yes, the middle of the night, so pray as much as you want until dawn comes. Then refrain from praying until the sun has risen, and as long as it looks like a shield until it becomes apparent. Then pray as much as you want until a pole stands on its shadow (i.e., noon), then refrain from praying until it has crossed the zenith, for Hell is heated up at midday. Then p
Grade: